Role of the Cysteinyl Leukotrienes in the Pathogenesis and Progression of Cardiovascular Diseases - Francesca Colazzo; Paolo Gelosa; Elena Tremoli; Luigi Sironi; Laura Castiglioni (Hindawi Limited, 2017)
Cysteinyl leukotrienes (CysLTs) are potent lipid inflammatory mediators synthesized from arachidonic acid, through the 5-lipoxygenase (5-LO) pathway. Owing to their properties, CysLTs play a crucial role in the pathogenesis of inflammation; therefore, CysLT modifiers as synthesis inhibitors or receptor antagonists, central in asthma management, may become a potential target for the treatment of other inflammatory diseases such as the cardiovascular disorders. 5-LO pathway activation and increased expression of its mediators and receptors are found in cardiovascular diseases. Moreover, the cardioprotective effects observed by using CysLT modifiers are promising and contribute to elucidate the link between CysLTs and cardiovascular disease. The aim of this review is to summarize the state of present research about the role of the CysLTs in the pathogenesis and progression of atherosclerosis and myocardial infarction.